Medcelične komunikacije na osnovi valov kalcijevih ionov - Kuk, Rok (Matrika, 2022)
A calcium ion wave is an increase in the concentration of these ions, which spreads to nearby cells. Cell regulation of Ca2+ is key for the functioning of organisms. Abnormal regulation of calcium ion concentration in cells causes a large number of diseases. This is why it is important to understand how cells regulate Ca2+ . This paper describes the basic physical mechanisms which cause changes of calcium ion concentration in cells and how cells use calcium waves for communication. A simplified mathematical model of Ca2+ regulation and diffusion is also presented.
Keywords: calcium ions; celična biologija; cellular biology; intercellular communication; intercellular waves; kalcijevi ioni; matematični model; mathematical model; medcelična komunikacija; medcelični valovi